Integrating Relevant Theories Of Critical Thinking With Pedagogical Principles And Practices In Teaching English - Tokumbetova Mehribonu Shavkat qizi (Zien Journals, 2024)
The development of critical thinking skills is a cornerstone of higher education, vital for students to navigate the complexities of modern information landscapes and societal challenges. In the context of teaching English, fostering critical thinking enhances students' analytical abilities, interpretative skills, and capacity for nuanced communication. This paper explores the integration of prominent critical thinking theories with established pedagogical principles and practical classroom strategies to create a robust framework for English language teaching (ELT). By examining theoretical underpinnings such as Bloom's Taxonomy, the PaulElder Framework, and Vygotsky's Socio-Cultural Theory, this study outlines how these models can inform and enhance pedagogical approaches including inquiry-based learning, problembased learning (PBL), collaborative learning, and reflective practice. Additionally, the paper discusses practical applications in the classroom, such as textual analysis, debates, reflective writing, and the use of multimedia resources, to cultivate a dynamic and engaging learning environment. The challenges of integrating these approaches, including institutional support, teacher training, and cultural considerations, are also addressed. Through a comprehensive review and practical insights, this paper aims to provide educators with effective strategies to develop critical thinking skills in their English language students, ultimately contributing to their academic success and lifelong learning capabilities.
Keywords: Critical Thinking; Pedagogical Principles; English Language Teaching